CHANGES OF SOIL FAUNA DIVERSITY IN SEVERAL TYPES OF SUPER WET TROPICAL RAIN FOREST AREA - Marsandi, Fenky; Hermansah; Agustian; Yasin, Syafrimen (International Journal of Research -GRANTHAALAYAH, 2019)
Land type changes in the super wet tropical rain forest area caused fluctuations in the diversity of soil fauna which caused disruption of ecosystem balance. This research was conducted for four months, in November 2017-February 2018. Data on soil fauna was taken using pitfall traps and hand sorting. Furthermore, the soil fauna data obtained were identified and calculated the value of the diversity index, evenness and dominance on each type of land for four months. The results showed that forests had a high diversity index of soil fauna, which were 3,134, 3,313 and 3,314 in the first to the third month. While in the 4th month the forest diversity index decreased to 2,981. In open land, the soil fauna diversity index value is moderate, which is 2.631, 2.998, 2.782 and the diversity index increases in the fourth month, is 3.084. Mixed gardens have a value of the fauna diversity index of 2,728, 3,113, 2,870 and increased in the fourth month of 3,084. Whereas monoculture gardens have diversity index values of 2,527, 3,214, 2,935 and 2,927. Changes in land types of super wet tropical rainforests have an effect on changes in the level of diversity of soil fauna and not always these changes reduce the level of diversity of soil fauna.